2020
DOI: 10.1002/pnp.682
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 on an early intervention in psychosis service

Abstract: Establishing the impact of the coronavirus disease 2019 (COVID‐19) pandemic on utilisation of mental health services is a potentially useful means of measuring the psychiatric consequences of the COVID‐19 pandemic and related lockdown. Here, the authors describe their study, which compared the use of an early intervention in psychosis service in the four weeks immediately prior to the COVID‐19 regulated lockdown in the UK, with the four weeks immediately subsequent to lockdown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Furthermore, consistent with the findings of Loughlin et al (2020), SUs valued support reintegrating into society once their care had ended. Finally, the statistically insignificant differences in satisfaction ratings between the current study and Watkins et al (2018) reinforce the findings of Chakraborty et al (2020) that outcomes for these EIP services do not appear to have diminished as a result of the pandemic, despite alternative methods of providing care.…”
Section: Comparison To Existing Literaturesupporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, consistent with the findings of Loughlin et al (2020), SUs valued support reintegrating into society once their care had ended. Finally, the statistically insignificant differences in satisfaction ratings between the current study and Watkins et al (2018) reinforce the findings of Chakraborty et al (2020) that outcomes for these EIP services do not appear to have diminished as a result of the pandemic, despite alternative methods of providing care.…”
Section: Comparison To Existing Literaturesupporting
confidence: 70%
“…Research into the impact of the Coronavirus pandemic found that whilst the percentage of referrals accepted by an EIP service remained consistent throughout the pandemic the overall number of total referrals received significantly decreased (Chakraborty et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in the weeks immediately subsequent to COVID‐19 lockdown, findings from both the UK and France show reduced utilisation of mental health services, including referrals and psychiatric hospital admissions, 14,15 as well as emergency psychiatric consultations 16 . It is unclear what the root causes of such findings are, and it is likely that there is a multifactorial relationship governed by factors such as public health messaging, occupational instability and changes to the health care workforce during this time 14 …”
Section: The Relationship Between Covid‐19 and Mental Illnessmentioning
confidence: 99%
“…In a retrospective study investigating patients admitted to acute mental health wards during a four week period in April-May 2020, Abbas and colleagues 13 observed that 31% of admitted patients exhibited psychiatric symptoms related to COVID-19 and/or the related lockdown measures. Interestingly, in the weeks immediately subsequent to COVID-19 lockdown, findings from both the UK and France show reduced utilisation of mental health services, including referrals and psychiatric hospital admissions, 14,15 as well as emergency psychiatric consultations. 16 It is unclear what the root causes of such findings are, and it is likely that there is a multifactorial relationship governed by factors such as public health messaging, occupational instability and changes to the health care workforce during this time.…”
Section: Indirect Psychiatric Effects Of Covid-19 Pandemicmentioning
confidence: 99%
“…In addition to having an impact on the physical health of the global population, pandemics can also have a substantial impact on mental health. This can be measured in a variety of ways, including numbers of new mental health service referrals, 3 psychiatric hospital admissions 4 and interview- and/or survey-based approaches.…”
mentioning
confidence: 99%